Desmoglein2 Regulates Claudin2 Expression by Sequestering PI-3-Kinase in Intestinal Epithelial Cells - Burkard, Natalie; Meir, Michael; Kannapin, Felix; Otto, Christoph; Petzke, Maximilian; Germer, Christoph-Thomas; Waschke, Jens; Schlegel, Nicolas (Frontiers in Immunology, 2021)
Inflammation-induced reduction of intestinal desmosomal cadherin Desmoglein 2 (Dsg2) is linked to changes of tight junctions (TJ) leading to impaired intestinal epithelial barrier (IEB) function by undefined mechanisms. We characterized the interplay between loss of Dsg2 and upregulation of pore-forming TJ protein Claudin2. Intraperitoneal application of Dsg2-stablising Tandem peptide (TP) attenuated impaired IEB function, reduction of Dsg2 and increased Claudin2 in DSS-induced colitis in C57Bl/6 mice. TP blocked loss of Dsg2-mediated adhesion and upregulation of Claudin2 in Caco2 cells challenged with TNFα. In Dsg2-deficient Caco2 cells basal expression of Claudin2 was increased which was paralleled by reduced transepithelial electrical resistance and by augmented phosphorylation of AKTSer473 under basal conditions. Inhibition of phosphoinositid-3-kinase proved that PI-3-kinase/AKT-signaling is critical to upregulate Claudin2. In immunostaining PI-3-kinase dissociated from Dsg2 under inflammatory conditions. Immunoprecipitations and proximity ligation assays confirmed a direct interaction of Dsg2 and PI-3-kinase which was abrogated following TNFα application. In summary, Dsg2 regulates Claudin2 expression by sequestering PI-3-kinase to the cell borders in intestinal epithelium.